2002
DOI: 10.1046/j.0001-5172.2001.00000.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum S100β protein and Mini‐Mental State Examination after cold (28°C) and warm (34°C) cardiopulmonary bypass using different blood gas strategies (alpha‐stat and pH‐stat)

Abstract: These results support the use of warm CPB (34 degrees C) in patients undergoing coronary artery bypass surgery regardless of the type of blood gas strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Correlations between deterioration in performance of the MMSE and elevations in S100β levels, similar to those found in the present study, have been reported after cardiopulmonary bypass surgery [2,3]. This has not been demonstrated after cardiac arrest and resuscitation [16], possibly due to the length of time that had elapsed between the event and MMSE testing or the small number of survivors available for testing.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Correlations between deterioration in performance of the MMSE and elevations in S100β levels, similar to those found in the present study, have been reported after cardiopulmonary bypass surgery [2,3]. This has not been demonstrated after cardiac arrest and resuscitation [16], possibly due to the length of time that had elapsed between the event and MMSE testing or the small number of survivors available for testing.…”
Section: Discussionsupporting
confidence: 84%
“…Its biological half-life is approximately 30 minutes [1]; hence, persistently increased levels of S100β indicate continuous release of this protein from damaged tissue. Elevated serum levels of S100β have been reported to correlate with neurological deterioration after cardiac surgery [2,3] and with poor likelihood of survival after hypoxia [4]. Serum protein S100β is also a recognised marker of traumatic brain injury [5-7] and blood-brain barrier dysfunction in the absence of apparent brain injury [8].…”
Section: Introductionmentioning
confidence: 99%
“…44 The conclusions of different studies regarding adequate hypothermic support to prevent major neurologic damage are contradictory, 48 -50 although, it seems that perfusion with mild hypothermia (33°C-35°C) decreases the cerebral risk of early neuropsychological dysfunction after cardiac Embolism is a principal source of neurologic damage. [51][52][53][54] The ideal temperature for noncomplex cardiac surgery procedures is still undetermined. Activation of the inflammatory response is associated to microembolic events and promotes cytotoxic and vasogenic edema, identified in autopsies after recent cardiac surgery and by noninvasive techniques such as diffusion-weighted magnetic resonance imaging or 1 H-magnetic resonance spectroscopy.…”
Section: Disorders In Neuronal Metabolism Secondary To Hypoxemia or Vmentioning
confidence: 99%
“…Only studies of patients undergoing coronary artery bypass grafting are listed in Table 3. Attempts were made to perform a power calculation for neurological outcome in some studies [11, 12] but not in others [13–17]. The studies listed in Table 3 are heterogeneous: most (but not all) were randomised; bypass temperatures ranged from 33 to 37 °C for warm bypass and 23–32 °C for cold bypass; some used early rewarming in the warm CPB group, others did not.…”
Section: Effects Of Cardiopulmonary Bypass Temperature On Neurologicamentioning
confidence: 99%
“…Protein S100β is a potentially useful early marker of brain damage. It has been used in attempts to differentiate between the benefits and adverse effects of different bypass temperatures [14, 27, 28]. Gao et al.…”
Section: Warm Vs Cold Cardiopulmonary Bypass and Protein S100β Levelsmentioning
confidence: 99%